Performance Of Vibration-Induced Electrode Plates In Batch Electrocoagulation For Stabilized Landfill Leachate Treatment - Hanif, Mohamad Haziq Mohd (2024)
The high strength of landfill leachate has limited the efficiency of electrocoagulation due to several drawbacks such as the passivation of electrodes and accumulation of bubbles at the surface of the electrode which increased the resistance of ions transfer. This study investigated the performance of batch electrocoagulation with vibration-induced electrode plates in the treatment of stabilized landfill leachate obtained from Pulau Burung Landfill to improve the removal of COD, colour and NH3-N removal. The preliminary study of the effect of interelectrode distance, current density and electrolysis time studied revealed that the removal of pollutants showed an increasing trend until reaching optimum conditions. Further experimental design involving the initial pH, vibration intensity and electrolysis time indicated that the optimum conditions were obtained at pH 4.4, 45 minutes and vibration intensity of 3.8V with 23.8% COD, 92.8% colour and 43.8% NH3-N, respectively. The optimum conditions setup was further analysed and compared with stationary electrocoagulation and electrocoagulation with aid of magnetic stirring at 200 rpm. Scanning electron microscopy (SEM) revealed that electrocoagulation with vibration-induced shows smooth and identical dents compared to other electrocoagulation intensification The degree of particle destabilization indicates that vibration-induced electrocoagulation obtained faster steady states compared to other electrocoagulation.